Surface-Applied Biosolids Enhance Soil Organic Carbon and Nitrogen Stocks but Have Contrasting Effects on Soil Physical Quality - Virginia L. Jin; Kenneth N. Potter; Mari-Vaughn V. Johnson; R. Daren Harmel; Jeffrey G. Arnold (Applied and Environmental Soil Science)
Mid- to long-term impacts of land applying biosolids will depend on application rate, duration, and method; biosolids composition; and site-specific characteristics (e.g., climate, soils). This study evaluates the effects of surface-broadcast biosolids application rate and duration on soil organic carbon (SOC) stocks, soil aggregate stability, and selected soil hydraulic properties in a municipally operated, no-till forage production system. Total SOC stocks (0–45 cm soil) increased nonlinearly with application rate in perennial grass fields treated for 8 years with 0, 20, 40, or 60 Mg of Class B biosolids (DM) ha−1 yr−1 (midterm treatments). Soil organic C stocks in long-term treatment fields receiving 20 years of 20 Mg ha−1 yr−1 were 36% higher than those in midterm fields treated at the same rate. Surface-applying biosolids had contrasting effects on soil physical properties. Soil bulk density was little affected by biosolids applications, but applications were associated with decreased water-stable soil aggregates, increased soil water retention, and increased available water-holding capacity. This study contrasts the potential for C storage in soils treated with surface-applied biosolids with application effects on soil physical properties, underscoring the importance of site-specific management decisions for the beneficial reuse of biosolids in agricultural settings.